The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1023/b:urol.0000032687.58462.4f
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of inducible nitric oxide synthase (iNOS) activity in the testicular dysfunction associated with varicocele: An experimental study

Abstract: Nitric oxide (NO) has been reported to be increased in the spermatic veins of men affected by varicocele. The aim of the present study was to determine whether iNOS (inducible nitric oxide synthase) has a role in testicular dysfunction associated with varicocele, immunohistochemistry analyze was used to study iNOS activity in testis of adolescent rats with experimental left varicoceles. Rats were randomly divided into three groups. The first group consisted of rats undergoing partial ligation of left renal vei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…In this regard, the damage caused by varicocele becomes worse as the time between its first appearance and varicocelectomy increases [149], indicating that the testes have intrinsic mechanisms for avoiding permanent damage under certain conditions, but that damage is inevitable when the hypoxia (or elevated temperature) is sustained over time. Changes in testicular tissue have been described in both humans and animal models of varicocele, particularly in rats, producing smaller testicles with a decrease in Leydig cell functioning and a low total sperm count but with no abnormalities in the motility or morphology of the spermatozoa [150152]. …”
Section: Local Hypoxia: Varicocele and Testicular Torsionmentioning
confidence: 99%
“…In this regard, the damage caused by varicocele becomes worse as the time between its first appearance and varicocelectomy increases [149], indicating that the testes have intrinsic mechanisms for avoiding permanent damage under certain conditions, but that damage is inevitable when the hypoxia (or elevated temperature) is sustained over time. Changes in testicular tissue have been described in both humans and animal models of varicocele, particularly in rats, producing smaller testicles with a decrease in Leydig cell functioning and a low total sperm count but with no abnormalities in the motility or morphology of the spermatozoa [150152]. …”
Section: Local Hypoxia: Varicocele and Testicular Torsionmentioning
confidence: 99%
“…Each isoform has a reductase domain that contains a compound known as tetrahydrobiopterin (BH4), which is essential for efficient production of NO [24,25]. Interestingly, a testis-specific subclass of nNOS, known as TnNOS, has been recently identified as a major contributor to the formation of NO [31-34]. TnNOS is found to localize solely in the Leydig cells of the testis, thereby suggesting its involvement in steroidogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that this form of NOS can be induced by factors released from round spermatids, implicating a regulatory role of germ cells on Sertoli and Leydig cell NOS function [20,34]. Overall, these three isoforms are found in various cells of the testis, including Sertoli cells, germ cells in the seminiferous epithelium, Leydig cells, myofibroblasts, myoid cells, endothelial cells, and spermatozoa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These theories include increased apoptosis, increased DNA damage in sperm, oxidative stress, tissue hypoxia, degenerative changes in the seminiferous tubule and immunological infertility caused by the increased apoptosis of germ cells. [4][5][6][7][8][9] However, the presence of a varicocele does not necessarily cause infertility or worsen semen viability. Therefore, further studies are still necessary to understand the relationship between varicoceles and male infertility.…”
Section: Introductionmentioning
confidence: 99%